Piezoelectric properties and domain configurations of PZT ceramic with NiO addition - N. Jaitanong (2018)
The effects of nickel oxide addition on the piezoelectric properties and domain configurations of lead zirconate titanate (PZT) ceramic were investigated. PZT with nickel additive having the compositions of (1-x) PZT-xNiO when x = 0, 0.02, 0.04, 0.06, 0.08, and 0.10. The piezoelectric properties (d33) of all ceramics were measured at room temperature using d33meter. The domain structure was observed using piezoresponse force microscopy (PFM). From the results, it could be seen that the properties of PZT ceramic with nickel addition changed significantly with regards to the sintering temperature and nickel content. © 2013 Copyright Taylor and Francis Group, LLC.